2020
DOI: 10.1093/icesjms/fsaa046
|View full text |Cite
|
Sign up to set email alerts
|

A combination of genetic and phenotypic characterization of spring- and autumn-spawning herring suggests gene flow between populations

Abstract: Atlantic herring (Clupea harengus) has complex population structure and dynamics including diverse life histories and spawning times with spring and autumn spawning as the most common modes. Originally, spawning herring were phenotypically identified based on their maturity development or otolith microstructure by determining seasonal specific larval growth patterns. Recently, genetic markers have revealed clear genetic differentiation between spring- and autumn-spawning populations. All three methods were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Selection studies comparing otolith growth of larvae and survivors (adults) on for example strong and weak year classes might reveal new insights on the recruitment dynamics of herring. Further, this validation strengthens other studies where conclusions are drawn from microstructure analysis of adult otoliths which have management (Clausen et al, 2007) or ecological (Berg et al, 2020b) implications.…”
Section: Discussionsupporting
confidence: 81%
“…Selection studies comparing otolith growth of larvae and survivors (adults) on for example strong and weak year classes might reveal new insights on the recruitment dynamics of herring. Further, this validation strengthens other studies where conclusions are drawn from microstructure analysis of adult otoliths which have management (Clausen et al, 2007) or ecological (Berg et al, 2020b) implications.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, examinations of the otoliths from fish in this sample, using the method by Clausen et al (Clausen et al, 2007), showed that they hatched in spring. Thus, this must represent a group of herring that has switched spawning season from spring to autumn, maybe because their nutritional status was insufficient to support spawning (McQuinn, 1997), demonstrating that spawning time in herring is controlled by a combination of genetic and environmental factors (Bekkevold et al, 2007;Berg et al, 2020).…”
mentioning
confidence: 99%
“…10 , showed that they hatched in spring. Thus, this must represent a group of herring that has switched spawning season from spring to autumn, maybe because their nutritional status was insufficient to support spawning 11 , demonstrating that spawning time in herring is controlled by a combination of genetic and environmental factors 12,13 .…”
Section: Resultsmentioning
confidence: 99%